Human Resources Management System At Police Resort Bengkulu Utara - Jufri Jufri; Slamet Widodo; Fachrudin Js Pareke (The Manager Review, 2023)
The purpose of the research was to describe how to arrange the police management system of human resource in the reformation era. Specifically, the study examined the aspects of the fulfillment and the reform of the police human resource management system. The Police officers who worked at the police headquarters in North Bengkulu Regency, termed Polres, treated as the sample in this study. The study employed a descriptive qualitative approach and used a survey questionnaire to collect the main data. The returned questionnaires that were filled out by 241 police, were then analysed using descriptive statistics of mean, percentage, and frequency. The results of the study show that in general the arrangement of the human resource management system has been going well. Of the six assessments on the fulfillment aspect, namely planning for personnel needs, patterns of mutation, personnel development, setting individual performance standards, enforcement of discipline, and personnel information systems, are in accordance with the Decree of the Chief of Police and ministerial regulations. However, from the aspect of reform, one out of three punishments, namely disciplinary violations, has not shown a significant reduction. Even though within the Polri organization there is an element of oversight, the control mechanism through SiPropam faces dilemmatic situations and conditions due to the influence of a sense of corps, seniority relations, and an excessive sense of loyalty to friends which makes it weak in its implementation. Likewise Kompolnas, which should be in Law Number 2 of 2002 concerning the Police to be formed as an external supervisor, in fact it is only formulated as an "advisor" to the president in the field of police and the people who receive complaints, which are injured by members of the National Police..   Keywords: Management System, Human Resources Management, Police, Reform